Innovative Approaches to Urban Drainage System : A Review - Muhammad Ade Kurnia Harahap; Loso Judijanto; Bucky Wibawa Karya Guna; Jasman; Ilham Samanlangi (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Conventional urban drainage systems are often unable to cope with extreme rainfall and rapid urbanization, resulting in flooding and water pollution. Innovative approaches are needed to improve the performance and sustainability of urban drainage systems. This research aims to explore and analyze innovative approaches in urban drainage systems to improve efficiency, sustainability and resilience to climate change. This type of research is literature research. Data collection techniques are direct observation through journal databases and documentation. Data analysis in the research is qualitative data analysis. The results concluded a promising innovative approach to improve the performance and sustainability of urban drainage systems. Integrated application of this innovative approach can help create more resilient, sustainable and environmentally friendly urban drainage systems, contributing to healthier and climate change resilient cities. Further research is needed to evaluate the long-term effectiveness and scalability of this approach in various urban contexts.